Evaluating the long-term outcomes of metabolic surgery in obesity management: effects on weight loss, comorbidities, quality of life, and sustainability of surgical interventions - Bhanja, Mrutyunjaya; Vaishnaw, Aayush (Journal of Neonatal Surgery, 2025)
Obesity has become a global health crisis, with significant associations to various comorbidities such as type 2 diabetes, cardiovascular diseases, and sleep apnea. While lifestyle changes and pharmacological treatments are commonly used for obesity management, metabolic surgery has emerged as a highly effective intervention. This study aims to evaluate the long-term outcomes of metabolic surgery in managing obesity, focusing on weight loss sustainability, improvement in comorbidities, quality of life, and the long-term sustainability of surgical interventions. The research is based on a retrospective analysis of patients who have undergone metabolic surgery, such as Roux-en-Y gastric bypass and sleeve gastrectomy, over a period of 5 to 10 years. The study examines several key outcomes, including sustained weight loss, resolution or improvement in comorbidities like type 2 diabetes, hypertension, and sleep apnea, and changes in the overall quality of life (QoL). Additionally, the study investigates complications, reoperation rates, and the long-term efficacy of these procedures. Findings reveal that metabolic surgery results in significant weight loss, with many patients maintaining a healthy weight long-term. The improvement or resolution of obesity-related comorbidities is prominent, particularly in the management of type 2 diabetes and hypertension. Quality of life scores show considerable improvements in both physical and psychological health. However, while metabolic surgery is associated with sustained benefits, the need for ongoing medical follow-up, dietary adjustments, and potential reoperations due to complications are important considerations for long-term success. This research highlights the importance of metabolic surgery as a transformative treatment for obesity and its comorbidities. It also underscores the necessity for a comprehensive post-surgery care plan to optimize long-term outcomes.